National Guidelines for Prevention and Control of Iron Deficiency Anemia in India - Bellad, Asha; Kapil, Radhika; Gupta, Aakriti (Indian Journal of Community Health, 2018)
Anaemia is a serious public health challenge in India with more than 50% prevalence across vulnerable groups such as pregnant women, infants, young children and adolescents. It has adverse effects on health, physical and mental productivity affecting quality of life. Guideline is any document containing recommendations about health interventions, whether these are clinical, public health or policy recommendations. The National Anemia Prevention and control guidelines have been developed taking cognizance of the current scientific evidence. The National Iron+ Initiative guidelines have been developed by the Adolescent Division of the Ministry of Health and Family Welfare (MoHFW), Government of India. Prevention and control of anaemia is one of the key strategies of the Health, Nutrition and Population Sector Programmes for reducing maternal, neonatal and childhood mortality and improving maternal, adolescent and childhood health status. It is estimated that anaemia causes 20 per cent of maternal deaths in India.